Resolusi Konflik Dunia Islam Diplomasi politik dalam Islam dan Relevasinya dengan Hubungan Internasional - dwisari, trirahayupujihastuti (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2024)
This article reviews Islamic Political Diplomacy and its Relationship to International Affairs. The political role of Islam is crucial in global diplomacy, used to support the interests of countries with an Islamic political identity. There is an explanation of strategies in various sectors aimed at national interests, as well as to improve the image of Islam in the international arena in order to achieve goals and build mutually beneficial relations with other countries. Islam according to International Relations theory is a concept of world challenges that focuses on relations between Muslim and non-Muslim environments and how these areas can be regulated. Based on this, this article will propose how the role of Islamic politics in diplomacy is used to support state interests? This problem will be studied using an international relations perspective. This article concludes that the role of Islamic politics in diplomacy reflects religious values and religious political realities and involves a balance between religious principles and political strategies to achieve national and global goals.